2000
DOI: 10.1023/a:1009523904786
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effect of Sahaja yoga meditation on 32 patients with primary idiopathic epilepsy on regular and maintained antiepileptic medication was studied. The patients were randomly divided into 3 groups: group I practiced Sahaja Yoga meditation twice daily for 6 months under proper guidance; group II practiced postural exercises mimicking the meditation for the same duration; and group III was the control group. Visual Contrast Sensitivity (VCS), Auditory Evoked Potentials (AEP), Brainstem Auditory Evoked Potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In five other papers [ 15 – 19 ] the approach taken was to have separate groups of participants. In only one trial [ 17 ] the participants were randomized as three groups. The advantage of the separate groups design over the self-as-control is that nonmeditators would not get inadvertently into meditation which is a disadvantage of the self-as-control design, where experienced meditators may get into the meditative state automatically, even during a control session.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In five other papers [ 15 – 19 ] the approach taken was to have separate groups of participants. In only one trial [ 17 ] the participants were randomized as three groups. The advantage of the separate groups design over the self-as-control is that nonmeditators would not get inadvertently into meditation which is a disadvantage of the self-as-control design, where experienced meditators may get into the meditative state automatically, even during a control session.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that Qigong meditation activates areas in the brainstem. There was no change in short latency auditory evoked potentials in patients with epilepsy who practiced Sahaja yoga possibly because they were novices to meditation [ 17 ]. In the other study which reported changes in short latency auditory evoked potentials the peak latency of wave V increased during random thinking, focusing and meditative focusing, but not during meditation [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Apart from meditation alone, a combination of yoga practices was shown to improve the sensitivity to a flickering light stimulus,[15] to reduce visual geometric illusions,[16] as well as to improve visual contrast sensitivity. [17]…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients usually report stress as a factor that increases the likelihood of auras or a seizure episode. [18] Panjwani[19] demonstrated that patients with epilepsy responded to Sahaja Yoga in reducing stress, in a randomized controlled study. This provides hope to patients with refractory epilepsy that non-pharmaceutical techniques may be successful in reducing seizure frequency.…”
Section: Epilepsymentioning
confidence: 99%